Upaya Merajut Kebersamaan dalam Kepemimpinan Perspektif Hadits - Ramdanil Mubarok (Indra Institute Research & Publication, 2023)
This research was written with the aim of knowing and describing hadith texts and their translations, ma'ani al-Mufradat, the content of hadith meanings, as well as efforts to knit togetherness in the jama'ah perspective of hadith. This study uses qualitative research with a type of literature study. The result is that the hadith texts related to togetherness, among others, are found in: Shahih Bukhari No. 6,532 and No. 6,610, Shahih Muslim No. 3.438, Musnad Ahmad No. 82 and 2.357, Sunan Darimi 2.407. The meaning of jama'ah in the hadith is: Al-Jama'ah is a group of people who are very large in number, a collection of priests from among the mujtahidin scholars, the companions in particular, a group of Muslims when they agree on one matter, Al-Jama'ah is Jama'atul Muslimin who agree on an emir. While the meaning of amir includes: a person who has influence in society, there is delegation of power and has power. Efforts that can be made in knitting togetherness in relation to the leader in the hadith include: praying for the leader, advising the leader, carrying out demonstrations according to the procedure, and not doing damage that only causes harm.